Search for Anomalous Top-Quark Couplings with the D0 Detector - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Neal, H. A.; et al. (Amer Physical Soc, 2009)
Anomalous Wtb couplings modify the angular correlations of the top-quark decay products and change the single top-quark production cross section. We present limits on anomalous top-quark couplings by combining information from W boson helicity measurements in top-quark decays and anomalous coupling searches in the single top-quark final state. We set limits on right-handed vector couplings as well as left-handed and right-handed tensor couplings based on about 1 fb(-1) of data collected by the D0 experiment.